Clinical Profile, Risk Factors and Quality-of-Life Burden of Foot Corns Among Adults in an Industrial Town of Tamil Nadu, India: A Community-Based Cross-Sectional Study - VIKRAM K.; SANTHYA S.; SAVITHA S.; VENKATESWARMURTHY N. (International Journal of Pharmacy and Pharmaceutical Sciences, 2026)
Objective: To evaluate the clinical profile, risk factors, functional impairment, and health-related quality of life associated with foot corns among adults in an industrial community in Tamil Nadu, India. Methods: A community-based cross-sectional study was conducted from October 2025 to March 2026. Using random household sampling, 272 adults aged ≥18 y with a clinically confirmed diagnosis of foot corns were recruited. Data were collected using a pre-tested semi-structured questionnaire and a standardised foot examination. Pain was scored on a 0–10 numeric rating scale (NRS), functional difficulty on a 0–15 composite score, and HRQoL using the validated RAND 36-Item Short-Form Health Survey (SF-36). Domain scores were compared with published Indian SF-36 reference values using one-sample t-tests; group differences and associations were assessed using the chi-square, Mann–Whitney U, Kruskal–Wallis and Spearman correlation tests. Statistical significance was set at p